The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/18069657rbcs20170399
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobial Inoculation and Molybdenum Fertilization in Peanut Crops Grown in a No Tillage System After 20 Years of Pasture

Abstract: Peanut (Arachis hypogea) is an important legume grain consumed by humans and utilized for effective nutrient cycling in a diverse cropping system. Areas that have been cultivated with perennial pasture for decades may have nutritional deficiencies and lack a sufficient population of atmospheric nitrogen-fixing bacteria. Molybdenum is an essential micronutrient that is part of the enzyme nitrogenase contained within symbiotic Bradyrhizobium bacteria, which are responsible for fixing nitrogen in legumes. Our obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
(86 reference statements)
0
13
0
Order By: Relevance
“…Crusciol et al. (2018) showed increases in grain yield of 621 kg ha −1 (24%) with foliar application of up to 200 g ha −1 of Mo compared with an unfertilized treatment. In this study, the inconsistent response to the application of Mo between the 2 yr of the experiment may be related to the correction of soil acidity carried out before the implantation of the crop, which may have resulted in greater availability of Mo in the soil.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Crusciol et al. (2018) showed increases in grain yield of 621 kg ha −1 (24%) with foliar application of up to 200 g ha −1 of Mo compared with an unfertilized treatment. In this study, the inconsistent response to the application of Mo between the 2 yr of the experiment may be related to the correction of soil acidity carried out before the implantation of the crop, which may have resulted in greater availability of Mo in the soil.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, significant increases were obtained by Quaggio et al (2004) in response to fertilization with 200 g ha −1 of Mo in a low-pH soil. Crusciol et al (2018) showed increases in grain yield of 621 kg ha −1 (24%) with foliar application of up to 200 g ha −1 of Mo T A B L E 3 Effect of molybdenum application and (co)inoculation of Bradyrhizobium spp. and/or Azospirillum brasilense on final plant stand (FPS), pod number per plant (PNP), grain number per pod (GNP), 100-grain weight (100-G), pod yield (PY) and grain yield (GY) of creeping peanut (Arachis hypogaea L. 'RUNNER IAC 886') grown in sandy soil from the Brazilian Cerrado during the two growing seasons compared with an unfertilized treatment.…”
Section: Grain Yield and Production Componentsmentioning
confidence: 99%
See 3 more Smart Citations